FAKTOR – FAKTOR YANG BERPENGARUH TERHADAP AUDIT DELAY DAN KOMITE AUDIT SEBAGAI VARIABLE MODERASI - Priti Siwa Linggam; Sukrisno Agoes (Jurnal Kontemporer Akuntansi, 2025)
1This study aims to analyze the effect of Institutional Ownership, Earnings Per Share & Financial Distress on Audit Delay moderated by the audit committee. 2This research was conducted using mining companies listed on the Indonesia Stock Exchange (IDX) in 2015 – 2019. 3The sample of this study was selected using the purposive sampling method 430 companies were obtained with a 5-year period, a total of 150 companies will be used as research objects. 5The research method used is 6Microsoft Excel and Economic Views (EViews) software to process and tabulate the data obtained. 7This study shows that Institutional Ownership has no effect on Audit delay, Financial Distress has no significant effect on Audit Delay, Earning Per Share has a significant effect on Audit Delay and the audit committee in this study is able to strengthen the influence of Financial Distress & Earnings Per Share on Audit Delay.8 The implication of this study is business needs to have a proper and efficient strategy in order to avoid the problem of audit delay.